2021
DOI: 10.3389/fcimb.2021.672355
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Microbiota in Patients With Eosinophilic and Non-Eosinophilic Chronic Rhinosinusitis With Nasal Polyps

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by Th2-skewed inflammation and increased colonization by Staphylococcus aureus. CRSwNP can be distinguished as eosinophilic (ECRSwNP) and non-eosinophilic (NECRSwNP) by the infiltration of eosinophils. The local microbiota plays an important role in the persistent inflammation of CRSwNP. To evaluate the bacterial community composition on the distinct types of CRSwNP patients, we collected nasal swabs from 16 ECRSwNP patients, 18 NECRSwNP patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…H T S [25,34,35,38,39,41,[43][44][45][46][47]50,51,61]. The risk of bias (methodological quality) was assessed using the Newcastle-Ottawa scale.…”
Section: Data Organization and Risk Of Bias Assessmentmentioning
confidence: 99%
“…H T S [25,34,35,38,39,41,[43][44][45][46][47]50,51,61]. The risk of bias (methodological quality) was assessed using the Newcastle-Ottawa scale.…”
Section: Data Organization and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Recently, an increasing number of studies have revealed an association between dysbiosis of microbial composition, but not the colonisation of specific bacteria in CRS 45 . However, due to the highly diverse and variable sinonasal microbiota between individuals, the microbiota results show great heterogeneity across studies 24,46 . Whether the dysbiosis of nasal microbiota is a treatable trait that requires further investigation.…”
Section: Bacterium Relevant Traitsmentioning
confidence: 99%
“…Many researchers have pointed out that upper airway microbiota dysbiosis seriously affects the health [ 2 , 3 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Published reports confirm the presence of bacterial disorder in the upper respiratory tract of patients with AR, CRS, and asthma ( Figures S1A and S2 ).…”
Section: Characteristics Of Bacterial Microbiome Changes In the Respi...mentioning
confidence: 99%
“…Prevotella is a representative of this trend in the phylum Bacteroidetes [ 1 , 2 , 20 , 21 , 31 , 32 , 39 , 41 ], while complex changes have also been found in genera of the phylum Firmicutes. Levels of Staphylococcus rise in both CRS and asthma patients [ 20 , 21 , 27 , 39 , 44 ], though the prevalence of this genus decreases in the upper airway of AR patients [ 17 ] and the levels of Staphylococcus aureus increase [ 19 , 25 , 29 , 32 , 38 , 47 ]. Furthermore, the prevalence of Streptococcus in the upper respiratory tract is higher in both CRS and asthma patients [ 28 , 29 , 36 , 43 ], while levels of Butyrivibro decline in AR and asthma patients [ 34 ].…”
Section: Characteristics Of Bacterial Microbiome Changes In the Respi...mentioning
confidence: 99%